ナンキョク サン ビサイ ソウルイ ノ バイヨウ 3 ナンキョク スカルブスネス ノ エンコ スリバチイケ ヨリ ブンリ シタ TROPIDONEIS LAEVISSIMA W G S WEST - 綿貫, 知彦; ワタヌキ, トモヒコ; 大野, 正夫; オオノ, マサオ; WATANUKI, Tomohiko; OHNO, Masao (国立極地研究所, 1976)
P(論文) The Lake Suribati is a salt lake (25-73 g Cl/l in a season) on the Skarvsnes of the coastal region of Lutzow-Holm Bay in Antarctica. Antarctic endemic diatom Tropidoneis laevissima W. & G. S. WEST was isolated from the samples of bottom sand which were collected on the coast of the lake on 28-29th of January in 1975 (Antarct. Rec., 54, 94-100). The length of the shell is 46-52μ and the width of the shell is 6-8.2μ. Striae are 22-26 in 10μ. This species grew very slowly and slightly in the fresh water of artificial culture medium, while it grew somewhat rapidly on the agar artificial culture medium with the lake water (30-50%) or NaCl (10-20%). This species is characterized by its halophic algae. departmental bulletin paper